ANALYSIS INDICATOR OF CRITICAL THINKING SKILLS IN PHYSICS TEXTBOOKS FOR SENIOR HIGH SCHOOL GRADE X SEMESTER 1 IN PADANG - Intan Purnama Yani; Rita Iranie; - Ratnawulan; Riri Jonuarti; Fanny Rahmatina Rahim (Universitas Negeri Padang, 2021)
This research aims to determine the availability of critical thinking skills indicators in physics textbooks for grade X semester one high-school physics used in Padang. This research is descriptive research with a qualitative approach. The data population in this study was all physics textbooks for Grade X semester 1 used in senior high schools in Padang. The research sample is the three physics textbooks that are most widely used in senior high schools in Padang. The data in this study were taken using critical thinking indicator analysis instruments in physics textbooks for grade X SMA with data collection techniques through documentation studies. Based on the results of the analysis of critical thinking skills indicators in the physics textbook for grade X semester 1, it was found that the physics textbook written by Marthen Kanginan published by Erlangga has the highest level of availability of critical thinking skills indicators with a percentage of 51.6% in the available category. In contrast, physics textbooks written by Aris Prasetyo Nugroho et al. and published by Mediatama have the lowest availability of critical thinking skills indicators with 29.6% with the less available category.